Identification of the single gene for calmodulin in Dictyostelium discoideum. - Goldhagen, H (1986)
We report the isolation and sequence determination of a cDNA containing most of the coding sequence for Dictyostelium discoideum calmodulin. The cloned cDNA was used as a probe to examine the complexity of D. discoideum genomic DNA. These studies indicated that D. discoideum cells possess a single calmodulin gene.